Dampak Pemotongan Anggaran terhadap Digitalisasi Birokrasi dan Keadilan Distributif di Daerah Tertinggal - Haryadi, Annisa Putri (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2026)
Bureaucratic digitization is part of the government's strategic plan to improve the effectiveness and quality of regional public services. The government's physical budget cuts have the potential to hamper the development of basic networks, data centers and technological facilities that are the foundation of digital services. The imbalance between digitalization ambition and regional capacity shows that the principle of distributive justice in budget allocation is not yet optimal, so that the risk of being digitally left behind is greater for regions that depend on central fiscal support. This study employs a qualitative-descriptive approach using policy analysis based on literature review and secondary data from academic publications, government reports, and relevant media sources. This analysis confirms that the success of bureaucratic digitalization is very dependent on infrastructure readiness, human resource capacity and the stability of regional financing. Physical budget cut policies need to be formulated proportionally so as not to widen disparities in public services and ensure they are inclusive and sustainable throughout Indonesia.